1987
DOI: 10.1016/0014-5793(87)81498-9
|View full text |Cite
|
Sign up to set email alerts
|

The primary reaction of photosystem II in the D1‐D2‐cytochrome b‐559 complex

Abstract: Flash-induced absorbance changes in the picosecond and nanosecond time range have been measured in the 'Dl-D2-cyt b-559 complex' isolated from photosystem II membranes. The results indicate the efficient formation of the primary radical pair P680' pheophytin-, which had a lifetime of about 36 ns, and the presence of unconnected chlorophyll in this preparation. It is concluded that the complex contains the active photosystem II reaction center, and that this reaction center contains at most 4 chlorophyll a mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(63 citation statements)
references
References 11 publications
7
55
1
Order By: Relevance
“…Therefore, we will restrict our analysis to the fast component, which we attribute to charge separation based on past work (37,45). Finally, the nondecaying component is believed to reflect the fully chargeseparated state of the RC (P680 ϩ -Pheo Ϫ ), which has a lifetime of 36 ns at ambient temperature (45,62,63).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we will restrict our analysis to the fast component, which we attribute to charge separation based on past work (37,45). Finally, the nondecaying component is believed to reflect the fully chargeseparated state of the RC (P680 ϩ -Pheo Ϫ ), which has a lifetime of 36 ns at ambient temperature (45,62,63).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Nanba and Satoh (24) reported the isolation of a PSII complex composed of Dl, D2, and Cyt b-559 which they identified as the RC. Danielius et al (9) confirmed this identification by showing that the material could transfer an electron from P680 to endogenous pheophytin. In this paper we confirm the isolation of the Nanba-Satoh preparation and report on several spectral properties that appear to relate to the stability of the isolated PSII reaction center.…”
mentioning
confidence: 85%
“…charge separated state of the RC (P680+-Pheo a-), which has been shown by nanosecond experiments to have a lifetime of 36 ns at ambient temperature [40]. The difficulties in reliably fitting a triple exponential decay with the modest signal-to-noise (typically about 50 at this pump energy) inherent in transient absorption experiments is well known.…”
Section: Kinetics At 544 Nm With 200 Nj Pump Pulsesmentioning
confidence: 99%